FROM OBJECT AND SUBJECT. SLAVERY, LEGAL CAPACITY AND THE BLURRING OF SERVITUDE IN LATE COLONIAL CHILE. - San Martín Aedo, William (Revista de Historia Social y de las Mentalidades, 2024)
Historians and social scientist have debated for several decades the understanding of black slavery in Latin America in terms of property and primarily defined by a dichotomic idea of “object” and “subject”. Following this debate, I further study combined legal and social aspects of slavery in late colonial Chile. This perspective demonstrates how legal rights and social practices were superimposed over definitions that understood slaves primarily as property. I argue that these notions and practices shaped an ambiguous social and legal entity, and challenged the internal borders of their objectuality and the relative limits of slavery. The analysis of slave litigation at the end of the 18th century in Chile reveals cultural and social practices that would question the idea of African descendants as an isolated group mainly defined by their legal status. Slaves and their relatives used their legal capacity being active agents within the judicial system. They displayed their ability to negotiate their status within the colonial state, and also they revealed their racially and socially diverse support networks. The study of these documents makes evident an intricate system of social and legal statuses as well as the process by which black slaves disappeared into a broader notion of servitude in late colonial Chile.